Analisis Data Eksploratorif Pada Studi Kasus US Flight Routes and Fares - Nathan Joshua (Universitas Kristen Maranatha, 2025)
The aviation industry is one of the sectors of the global economy that has a huge influence, for the United States itself aviation is one of the largest economic sectors, ranging from national to international flights with uncertain distribution of flight ticket prices. The analysis was conducted to find the determining factors to the main factors that determine the price of domestic flight tickets in the United States. The analysis was carried out using the EDA (Exploratory Data Analysis) method, and combined with feature engineering, external data in the form of news, and relevant articles. There are several findings obtained after analysing the US Flight Routes and Fares (1993-2023) dataset, which is a dataset that accommodates domestic flight records of the United States. The discovery obtained is that flight ticket prices will be more expensive if you use exclusive airports as origins or destinations, there are also some airports that have high flight ticket prices due to things such as strategic places and local government policies that make flight ticket prices expensive. The choice of city affects the price of airline tickets, but the more popular the city is, it doesn't make it more expensive, like Los Angeles, and New York is a popular city, but it doesn't make it to the list of cities that have expensive flight ticket prices. The number of flight distances does not determine the price of the flight ticket, but the flight ticket price for a flight distance above 1118 miles, which is the average in the dataset, has a high average flight ticket price. Major events such as Covid-19, 9/11, and Inflation greatly affect the ups and downs of flight ticket prices, as evidenced by the fact that in 2020 when Covid-19 was rampant, several airports issued policies to restrict flights which made flight activities difficult, lack of interest, and staff shortages that made flight ticket prices very low. The choice of time (quarter) affects the price of flight tickets, flight ticket prices will increase during national holidays such as during the 3rd quarter or at the time of summer holidays, making demand high and of course increasing flight ticket prices. Explicitly, no prominent factors were found, but by combining several factors such as the selection of cities, airports, and flight times, a trend or pattern for flight ticket prices will be obtained